Analisis Semiotika Ayat Akuntansi Dalam Al Qur’an - Mustamin, Asyraf; Sudirman, Sudirman (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
This study discusses accounting in Islam in the semiotic analysis of the Qur'an. As for the motivation that drives the choice of this problem, accounting has so far been only seen as a means of satisfying the financial satisfaction of the owners of capital, even though there are many verses of the Al-Qur'an that discuss much more about accounting in Islam. Islam is sourced from the Al Qur'an Al Karim in verses that talk a lot about things and the Al Qur'an. Analysis of the verses of the Qur'an which contain the idea of ​​Islamic accounting needs to be analyzed from various disciplines of the Qur'an and linguistics of the Qur'an. Semiotics is an Islam that discusses signs and markers in communicating. In studies and research to apply how semiotic theory is applied to try to analyze the linguistic signs of accounting in the Al-Qur'an. The concept of Islamic accounting in the Al-Qur'an uses symbolic significance which is a world of text meaning with a natural sign which is part of the physical world which is used as a means of deliberate and conscious communication spontaneously and unintentionally in responding to stimulation. Symbols, signs, signs, symbols are parts of the elements of signs and markers that are used in the Al-Qur'an to show the meaning of Accounting in the Qur'an. All of the above from the symbol and significance of signs and markers are indisputable signs of Islamic accounting.